2012
DOI: 10.31285/agro.16.688
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tillage on some soil chemical properties and Eucalyptus grandis growth

Abstract: Afforestation has increased rapidly in Uruguay since the Congress in1989 passed a law that promotes commercial forestation. This has raised public questions about the long term effects of forestation on soil quality and tillage requirements. The objective of this work was to evaluate the effect of tillage intensity on some soil chemical properties and wood production. The experiment was carried out in a Mollic Hapludalf , and planted with Eucalyptus grandis in 1992. A randomized complete block design with thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The establishment and growth of eucalyptus are favored by soil tilling, which can increase the productivity of forest stands (Prevedello et al, 2013). On the other hand, Pérez Bidegain et al (2012) found no-tillage system did not affect Eucalyptus grandis productivity in the first rotation in a mollic Hapludalf, and it was impossible to obtain adequate timber production with the use of reduced tillage.…”
Section: Tillage and Productivity In Soils Under Undulated Relief Wit...mentioning
confidence: 99%
“…The establishment and growth of eucalyptus are favored by soil tilling, which can increase the productivity of forest stands (Prevedello et al, 2013). On the other hand, Pérez Bidegain et al (2012) found no-tillage system did not affect Eucalyptus grandis productivity in the first rotation in a mollic Hapludalf, and it was impossible to obtain adequate timber production with the use of reduced tillage.…”
Section: Tillage and Productivity In Soils Under Undulated Relief Wit...mentioning
confidence: 99%